Identification of Individuals at Risk of Developing Type 2 Diabetes - Belkis Vicente Sánchez; Ernesto Vicente Peña; Aylín Altuna Delgado; Miriam Costa Cruz (Revista Finlay)
Background: to prevent type 2 diabetes, it is necessary to identify at-risk individuals and implement standardized screening methods that can be applied in different population segments anywhere in the world. Objective: to identify individuals at risk for type 2 diabetes in the general population. Methods: a cross-sectional study was conducted in nondiabetic individuals served by the family doctor-and-nurse offices No. 32 and 33 of the Cecilio Ruiz de Zárate Polyclinic in Cienfuegos between October 1st, 2011 and May 31st, 2013. The study population consisted of 2032 people aged 15 and over distributed by sex and age groups and the stratified sample included 670 people. The variables were: age, sex, body mass index, waist circumference and nutritional assessment. The Finnish Diabetes Risk Score was used and a glucose tolerance test was applied to those at high and very high risk. Results: females and normal weight individuals predominated. Mean age was 46.57 years and the mean waist circumference was 90.37 cm. Eleven participants had an abnormal glucose tolerance test. Ninety-one percent had low to moderate risk and 66.2 % performed physical exercises daily. Only 13 % were taking antihypertensive drugs and 4 % of the total has had high blood sugar levels at some point. Conclusions: low and slightly elevated risk of developing type 2 diabetes predominated in the study population according to the results of the score applied. Overweight and abnormal waist circumferences were the most common risk factors.